Development of database acquisition system for external balance device in low-speed wind tunnel - Abu Bakar, Hafizal (2011)
Wind tunnel is an essential tool for aerodynamic testing. To keep them operating in good condition, it is required a balance device. Unfortunately, not all wind tunnels that available in market are equipped with the balance unit. With availability of high technology manufacturing equipment such as Computer Aided Drawing (CAD) I Computer Aided Manufacturing (CAM) machine there is possibility to build and fabricate the balance device by the user themselves. However, a lack of knowledge on calibration and validation of balance device could be a potential obstacle to a success on balance device development. Moreover the knowledge on design and fabrication of balance device is limited to be a published to public due to its commercial matters. The purpose of this study is to develop a database acquisition system for external balance device for low speed wind tunnel. To calibrate and validate the external balance with database acquisition system a known weight is used.Then the external balance with database acquisition system is tested at low speed wind tunnel in order to investigate the aerodynamic characteristic on circular cylinder model and NACA0012 aerofoil model. The studied was done by developing the external balance device with database acquisition system. The database acquisition system was fabricated and tested on the external balance using a simulation fault test on control panel. After that, the fabricated external balance with database acquisition system is calibrated and validated using known weights. The tests were carried out by comparing against the reading from the external balance database acquisition system with apply loads on lift and drag axis using calibration arms. To measure the accuracy of external balance database acquisition system, an aerodynamic experiment on the circular cylinder model and NACA0012 aerofoil model is performed at a low speed wind tunnel. The aerodynamic experiments on a circular cylinder model and NACA0012 aerofoil model are used to determine the aerodynamic force of drag coefficient and lift coefficient and then it is compared with other existing test data. The results showing that the accuracy of the external balance database acquisition system on lift force and drag force at 99.9% and 100% of each respectively. The drag coefficient of circular cylinder at Reynolds number 2.05 x 104 , 2.20 X 104 , 2.36 X 104 , 2.51 X 104 , 2.59 X 104 and 2.75 x 104 were recorded at 1.02, 1.02, 1.00, 0.99, 1.06 and 1.06 respectively. For NACA0012 aerofoil, the lift coefficient and drag coefficient is recorded at Reynolds number 1.036 x 105. For Cli CD ratio at angle of attack range from 0° - 12° the recorded value is smaller than the published data due to low Reynolds number effects. However for angle of attacks 14°, 16° and 18° the data for Reynolds number at 3.6 x 106 and 1.036 x 105 is given the value 3.08, 2.60, 2.31 and 2.5, 2.6, 2.1 respectively which showing the balance reading is nearly same with published data. From the results, we conclude that the external balance database acquisition system has been successfully developed.